DAMPAK PEMBELAJARAN BERBASIS BUDAYA DI SEKOLAH DASAR - Hayati, Rahmi; Husnidar; Novianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Culture-based learning in elementary schools is an approach that integrates local cultural values ​​in the educational process to enrich the learning experience and shape the character of students. This research aims to identify the impact of implementing culture-based learning on students, teachers, schools, communities and the national education environment. The research results show that culture-based learning can increase cultural understanding, learning motivation, and students' academic and non-academic achievements. For teachers, this approach encourages creativity, innovation and strengthening relationships with students. Schools that integrate local culture can also enhance their identity as centers for cultural preservation and strengthen ties with the community. In addition, culture-based learning enriches the national curriculum and increases pride in Indonesia's cultural diversity. Based on these findings, it is recommended to develop culture-based learning modules, increase teacher capacity through training, strengthen collaboration between schools and communities, and develop policies that support the implementation of local culture in education. Thus, culture-based learning can make a major contribution to forming a generation with character and respect for Indonesia's cultural diversity